Utilization of a submersible pump as a plankton sampler for low-cost ecology practicum - Dhiyauddin Aridhowi; Sitoresmi Prabaningtyas; Rina Tri Turani Saptawati; Diah Ayu Eka Fitriana; Yuslinda Annisa (Labor Dasar dan Sentral Universitas Andalas, 2021)
The Van Dorn Bottle-water sampler which was operated during the plankton sampling practicum at the Department of Biology, FMIPA, State University of Malang experienced various obstacles, such as the tool being too heavy to use, difficulty opening and pouring water into the bottle, and the water sample bottle cap prone to falling and lost. These constraints affect the sampling of plankton that is less than optimal. Modification and use of the submersible pump is expected to replace the Van Dorn Bottle-water sampler to maximize plankton sampling. The submersible water collection pump is designed using five basic components, namely: a submersible pump, elastic-plastic hose, flow meter, timer, and battery power source, and can be used for various types of waters. Submersible pump trials were carried out at Ranu Grati lake, Pasuruan, East Java. The test results can be seen that the operation of the water pump is 5.9 kg lighter, can take more samples than the van dorn bottle-water sampler by 19.6 times and can take samples 35 seconds faster in each replication. With these advantages, the submersible pump can be used in plankton sampling practicum activities.